The Social Challenge in Times of COVID-19 - Commission économique pour l'Amérique latine et les Caraibes (United Nations, 2020)
This Special Report is the third in this series on the evolution and impacts of the COVID-19 pandemic in Latin America and the Caribbean. The coronavirus disease (COVID-19) pandemic has severe health effects and serious implications for economic growth and social development. It has arrived in Latin America and the Caribbean in a context of low growth —as analysed in the previous special reports on the subject— and, above all, of marked inequality and vulnerability, with growing poverty and extreme poverty, weakening of social cohesion and expressions of social discontent. Quarantines and physical distancing measures, which are needed to stop the rapid spread of the coronavirus and save lives, are leading to job losses (11.6 million more unemployed in 2020, compared to 2019) and reducing personal and household labour income. The loss of income is primarily affecting the broad strata of the population that are living in or vulnerable to poverty, and people working in activities that are more exposed to layoffs and pay cuts and, in general, those in precarious employment. In view of the major persistent gaps that the pandemic has widened, ECLAC reiterates that it is time to implement universal, redistributive and solidarity-based policies with a rights-based approach, to ensure that no one is left behind.